PRINCIPLES REGARDING THE ACTIVITY OF BODIES AND INSTITUTIONS THAT IMPLEMENT CRIME PREVENTION IN THE LAW AND PARTICIPATING IN IT - Очилова Ситора Салим кизи (Bright Mind Publishing, 2025)
This article analyzes the main legal and organizational principles of the activities of state bodies and institutions involved in the prevention of crimes. Based on the current legislative framework of the Republic of Uzbekistan, the legal status, powers and principles of operation of coordinating and executive bodies in the field of prevention are revealed. In particular, such principles as legality, openness, humanism, and protection of the rights and freedoms of citizens are separately highlighted. At the same time, proposals and recommendations are put forward to increase the effectiveness of cooperation and coordination mechanisms in the system.
Keywords: Crimes, prevention, principles, state bodies, institutions, legality, humanitarianism, legal foundations, cooperation, powers.